Global burden of HIV, syphilis, and HBV infection among women of childbearing age and children under five: based on the Global Burden of Diseases Study 2021 - Lian, Jia; Ke, Bihong; Zhang, Xiaosheng; Li, Jinbo; Li, Yandi; Wang, Keke; Feng, Yongliang; Wang, Suping (Frontiers in Public Health, 2025)
IntroductionHuman immunodeficiency virus (HIV), syphilis, and hepatitis B virus (HBV) infection pose a major global public health challenge. However, high-quality integrated data on the burden of these diseases among women of childbearing age (WCBA) and children remain limited. This study aims to provide a comprehensive global assessment of HIV, syphilis, and HBV infection among WCBA and children under five and to explore their potential relationships.MethodsThe Global Burden of Disease Study 2021 provided data on the global prevalence of WCBA and incidence of HIV, syphilis, and HBV infection in children under five years old from 1990 to 2021. Temporal trends were analyzed using annual average percentage change (AAPC) and joinpoint regression. A Bayesian age-period-cohort model was used to forecast the disease burden from 2022 to 2030.ResultsIn 2021, the age-standardized prevalence (ASPR) of HIV infection among WCBA was 830.87 per 100,000, while the age-standardized incidence (ASIR) of HIV among children under five was 15.39 per 100,000. From 1990 to 2021, the ASPR of HIV in WCBA demonstrated sustained growth, whereas the ASIR in children exhibited a rise-then-fall pattern. For syphilis, the 2021 ASPR among WCBA was 1057.32 per 100,000, and the ASIR in children was 58.36 per 100,000; both metrics followed a declining-then-rising trend, returning to 1990 levels by 2021. Both the ASPR of HBV infection among WCBA and the ASIR among children under five declined significantly from 1990 to 2021, with average annual percentage changes of −1.25% and −4.14%, respectively. Generally, ASPR and ASIR decreased as the sociodemographic index (SDI) increased. Regions with lower SDI experienced a disproportionately higher burden of HIV, syphilis, and HBV infections.ConclusionIn 2021, the global disease burden of HIV, syphilis, and HBV infection remained high among WCBA and children under five, with significant regional and demographic disparities. These findings indicate a persistent public health challenge, necessitating continued global efforts to mitigate the burden through addressing socioeconomic inequalities, strengthening health education, and expanding healthcare access.